Tracing the Normative Framework of South Africa s response to Early Childhood Development and Long-Term Care During the COVID-19 pandemic - Kasan, Juhi (Department of Sociology, 2025)
The COVID-19 pandemic has laid bare the crucial role of social care and its fundamental importance in shaping our lives. This research employs a critical political ethics of care approach to evaluate the South African government's response to mandated social care provision during the pandemic. Through a systematic analysis of the state's actions in managing and coordinating Early Childhood Development programs and Long-Term Care facilities for Older Persons throughout the COVID-19 pandemic, this investigation uncovers a pervasive lack of attentiveness, responsibility, competence, and responsiveness. Furthermore, this study delves into the factors contributing to the neglect of these vital care sectors. To do so, it examines the normative approaches to care as delineated in policy documents. Specifically, this research draws upon the White Paper on Social Welfare (1997) and the White Paper on Families (2013) to contextualise the government's response and reveal a predominant familialist approach to care. Within these documents, the study employs the insights of Selma Sevenhuijsen and colleagues (2003) and the Trace method to unearth the conceptualization of welfare and the allocation of caregiving responsibilities. Finally, the research investigates the correlation between the state's response to Early Childhood Development programs and Long-Term Care facilities and the rhetoric, norms, and discourses embedded in the aforementioned policy documents.